Gene expression analysis in predicting the effectiveness of insect venom immunotherapy - Niedoszytko, Marek; Bruinenberg, Marcel; de Monchy, Jan; Wijmenga, Cisca; Platteel, Mathieu; Jassem, Ewa; Oude Elberink, Joanne N.G. (Journal of allergy and clinical immunology, 2010)
Venom immunotherapy (VIT) enables longtime prevention of insect venom allergy in the majority of patients. However, in some, the risk of a resystemic reaction increases after completion of treatment. No reliable factors predicting individual lack of efficacy of VIT are currently available. To determine the use of gene expression profiles to predict the long-term effect of VIT. Whole genome gene expression analysis was performed on RNA samples from 46 patients treated with VIT divided into 3 groups: (1) patients who achieved and maintained long-term protection after VIT, (2) patients in whom insect venom allergy relapsed, and (3) patients still in the maintenance phase of VIT. Among the 48.071 transcripts analyzed, 1401 showed a >2 fold difference in gene expression ( P < .05); 658 genes (47%) were upregulated and 743 (53%) downregulated. Forty-three transcripts still show significant differences in expression after correction for multiple testing; 12 of 43 genes (28%) were upregulated and 31 of 43 genes (72%) downregulated. A naive Bayes prediction model demonstrated a gene expression pattern characteristic of effective VIT that was present in all patients with successful VIT but absent in all subjects with failure of VIT. The same gene expression profile was present in 88% of patients in the maintenance phase of VIT. Gene expression profiling might be a useful tool to assess the long-term effectiveness of VIT. The analysis of differently expressed genes confirms the involvement of immunologic pathways described previously but also indicates novel factors that might be relevant for allergen tolerance.